Policy Analysis For The Development Of Islamic Religious Education In Public Schools And Colleges - Hamza, Darwisa (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2024)
This study aims to analyze policies for the development of Islamic religious education in schools and public universities (PTU). Islamic religious education plays an important role in shaping student character, strengthening religious values, and providing a better understanding of the Islamic religion. However, there are challenges faced in developing Islamic religious education, such as lack of resources, inadequate curriculum, lack of qualified teachers, or lack of student interest in Islamic religious subjects. The research methods used in this study involve literature reviews, policy analysis, and primary data collection through interviews or surveys. Data is collected from various sources, including government policies, curriculum guidelines, related research reports, and opinions of relevant stakeholders. The results of this study indicate that Islamic religious education needs to be strengthened in schools and Public Universities through policies that focus on the inclusion of Islamic religious subjects in the curriculum, development of relevant curricula, provision of adequate resources, good teacher training, supervision and rigorous evaluation, collaboration with religious institutions, and better interfaith understanding. This study provides recommendations for improving the development of Islamic religious education, including expanding educational resources, increasing teacher training, revising the curriculum, developing interesting and interactive teaching methods, increasing student participation in religious activities, and using technology in Islamic religious education. In conclusion, the development of Islamic religious education in schools and public universities requires policies that focus on quality teaching, adequate resources, collaboration with religious institutions, and interfaith understanding. Implementation of this policy will play an important role in shaping student character, strengthening religious values, and providing a better understanding of the Islamic religion.